Kecernaan Nutrien Domba Fase Akhir Kebuntingan yang Diberi Ransum Flushing dengan Frekuensi yang Berbeda: Nutrient Digestibility of Local Ewes in Late Pregnancy Phase Fed by Flushing Ration with Different Feeding Frequency - Aulia Nurul Saputri; Dewi Apri Astuti; Dilla Mareistia Fassah (Jurnal Ilmu Nutrisi dan Teknologi Pakan (Nutrition and Feed Technology Journal), 2022)
The aim of this research was to evaluate the nutrient digestibility of late pregnancy local ewes treated with flushing ration and different feeding frequency. Twelve local ewes in the late pregnancy phase (BW 49.96 ± 9.67 kg) were divided on a Randomized Block Design with 4 treatments and 3 replications. The treatments were P1 (without flushing), P2 (flushing at the before and after mating), P3 (flushing at the before and after mating, and middle of pregnancy), and P4 (flushing at the before and after mating, middle, and late of pregnancy). Flushing concentrate containing 2% coconut oil and 5% lemuru fish oil. The variables observed were nutrient consumption and nutrient digestibility. The data were analyzed by using ANOVA, the data with significant differences in the treatment effects were further tested using Duncan Test. The result showed that the treatments significantly affected (p<0.01) consumption of crude fat. Giving the flushing ration at the before and after mating, and mid pregnancy significantly increased (p<0.05) digestibility of dry matter, crude protein, crude fiber, and N-free extract. It can be concluded that the feeding frequency of flushing affects the consumption and digestibility of local sheep at the late stages of pregnancy. Giving flushing ration at the before and after mating, and middle of pregnancy showed the best digestibility of dry matter, crude protein, crude fiber, and N-free extract. Key words: flushing, lemuru fish oil, local ewes, nutrient digestibility